2015
DOI: 10.12659/msm.893589
|View full text |Cite
|
Sign up to set email alerts
|

Does Corneal Hysteresis Correlate with Endothelial Cell Density?

Abstract: BackgroundOur aim was to determine if there is a correlation between corneal biomechanical properties, endothelial cell count, and corneal pachymetry in healthy corneas.Material/MethodsNinety-two eyes of all subjects underwent complete ocular examination, including intraocular pressure measurement by Goldmann applanation tonometer, objective refraction, and slit-lamp biomicroscopy. Topographic measurements and corneal pachymetry were performed using a Scheimpflug-based (Pentacam, Oculus, Germany) corneal topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…The biomechanical properties of cornea as CH and CRF are strongly correlated with CCT [46, 18]. The results of this study were in accordance with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…The biomechanical properties of cornea as CH and CRF are strongly correlated with CCT [46, 18]. The results of this study were in accordance with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Our study has found statistically significant, moderate-to-strong correlations between CH and CRF and endothelial cell count and variability. However, to the best of our knowledge, these findings differ from those in the literature, where no significant correlation has been found between biomechanical and endothelial corneal parameters in healthy volunteers [ 39 ] or in patients with cataract [ 40 ]. As the level of corneal hydration, which is regulated by the endothelial pump function, may influence corneal biomechanics [ 39 ], more studies are needed in order to identify the factors that modulate the relationship between CH, CRF and endothelium parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…The recent studies (since 2015), which have analyzed the mechanical corneal properties in relation with the cell density of the corneal endothelium, have been unable to show a statistically significant correlation [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%